Post monsoon tropical cyclone activity in the north Indian Ocean in relation to the El Nion / southern Oscillation phenomenon (MAUSAM, 1989)
In this paper the relationship between post monsoon (Oct-Dec) tropical cyclone activity in the north Indian Ocean and El Nino Southern Oscillation (ENSO) is discussed. The study uses a 83-year {1901-1983) time series or number of storm days for preliminary analysis. On an average the number of storm days during El Nina year is not departed from the normal. Usin9 the 48-year. (1935-1982) time series of number of storm days correlations were calculated with southern oscillation index (mean sea level pressure difference between Tahiti and Darwin) before, during and after the season: A weak negative correlation is seen between the storm activity and SOI before the season. Stability of correlations is examined by recalculating correlations using four 12-year data subsets. Magnitude of correlations is found to vary significantly in the subsets. There is no appreciable difference between the strike rate (number of storm crossing the coast/total number of storms) per El Nina year and strike rate per non El Nina year. There is no marked shift in the area of formation of storms during El Nino years from the climatologically favourable area: